Revisão sistemática de modelos experimentais para pesquisa em pavimentos permeáveis - BLANSKI, Mateus (2021)
With the evolution of urbanization, the accelerated growth of cities and the change in land use and occupation, negative changes occur in the natural characteristics of water resources. The increase in population density in urban centers causes vast soil sealing and, consequently, changes in the natural hydrological cycle, which leads to increased flooding, especially in large cities. Traditional urban drainage, with the use of waterproof surfaces and the surface runoff distribution system for drainage galleries, is one of the main reasons for the problems of flooding and lack of runoff control. Therefore, there was a need for the emergence of flood control measures, in which the permeable pavement stands out, as a control measure at the source. Knowing this, the present work aims to carry out a systematic review in the literature of experimental models for research on permeable pavements, seeking to compare the results found in the international literature and identify the main characteristics of the pavements. Thus, it was found that the porosity and water/cement ratio of the pavements has a big influence on the structural and hydraulic characteristics, in addition to concluding that modified permeable pavement projects must be tested and validated in Brazil, given their advantages over the common pavement and the traditional permeable pavement.